ANALISIS PENINGKATAN BRAND AWARENESS TEKNIK INDUSTRI MENGGUNAKAN SWOT DAN QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) - Adireja, Suprayogi Chandra (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
There are many universities in Indonesia that has The Department of Industrial Engineering of University X, the recent year of 2015 Industrial Engineering Major are registered in 187 universities. One of the universities that has Department of Industrial Engineering is the University X. The Department of Industrial Engineering of University X has got A accreditation, however the general public still not known and understand what it is The Department of Industrial Engineering of University X. There are only 6 out of 100 respondents who want to enter the Department of Industrial Engineering in University X, and 54% did not understand what is The Department of Industrial Engineering of University X, based on the distributed questionnaires. The research implemented SWOT and QSPM strategy which is conducted in order to be able to assess the increasing level of brand awareness in The Department of Industrial Engineering of University X. The first of the questionnaire distribution is to know the curent existence of brand awareness of The Department of Industrial Engineering of University X with the respondents are high school students. The second questionnaire was conducted to find out whether internal or external factors that exist within the Department of Industrial Engineering of University X may become strength or weaknesses. With the internal and external factors that has been provided, SWOT strategy can be implemented. Such action are implemented because the Department of Industrial Engineering University X is positioned within the first quadrant which the SO strategy can be used and assigned to the QSPM. SO strategy is the right thing to be done by the Department of Industrial Engineering University X based on SWOT Analysis. Strategy such strategy includes: 1) socializing the achievement of The Department of Industrial Engineering of University X which has been accredited A and has GPA average above 3 to the prospective students. 2) increasing the number of lecturers involved on Joint research to lecturers post-graduate and doctorate program. 3) achieving international level accreditation. 4) increase the number of cooperation with International industry. 5) increase and concurrent cooperation in the field of education, research, and community service with external parties both national and international level. 6) to make Industrial Engineering graduates who are in national or international industry to help fill guest lecture at Department of Industrial Engineering University X. based on QSPM method the highly recommended strategy is to increase the accreditation to the international level. Other recommended strategies are the improvement and sharing of cooperation in the field of education, research, and community service with external parties, both at national and international levels, and increasing number of lecturers involved in joint research on the lecturers of post-graduate and doctorate program